The road to the hoop: relative age effects and game-related performance in youth basketball - Bilgiç, M.; Brustio, P. R.; Ugurlu, A.; Isin, A. (Perceptual and Motor Skills, 2025)
Relative Age Effects (RAEs) have been widely reported trends in basketball participation, but research on the relationship between RAEs and competitive performance has been contradictory. We aimed to determine the magnitude of RAEs in elite youth basketball players and to analyze RAEs on key performance indicators (KPIs). We recorded and analyzed the incidence of early birthdates and the KPIs of 2487 youth basketball players (aged 16-19 years). We evaluated RAEs by means of the incidence of early birthdates using (i) Chi-square goodness-of-fit tests to compare player differences in birthdate quartiles and (ii) Poisson regression analysis to evaluate birthdates as a continuous variable. We conducted Kruskal-Wallis tests separately for each age group to assess possible relationships between birthdate quartile differences and KPIs. We observed consistent moderate RAEs across all ages. The Poisson regression analysis showed that athletes born near the beginning of the year were 4.6-8.4 times more likely to have been included on the squad than athletes born towards the end of the year. We observed no significant differences between KPIs for differently aged athletes. However, 16-year-old athletes with first quartile birthdates showed higher KPIs than those with fourth quartile birthdates of the same calendar year. The potential bases for RAEs are complex and include the characteristic demands of sports competition at various competition levels and athletes` ages, individual factors and social factors. We discuss these and other potential bases. Basketball coaches and managers should keep RAEs in mind when selecting youth players to avoid a selection bias towards players born at the beginning of the year which may close out training opportunities and cause drop outs for talented but slightly younger players.